2023
DOI: 10.3390/cancers15061780
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Patient’s Age and Head and Neck Cancer Treatment Decision—A Population-Based Diagnoses-Related Group-Based Nationwide Study in Germany

Abstract: Investigations on the association between patient’s age and head and neck cancer (HNC) treatment decision are sparse. Nationwide diagnoses-related group-based data of 1,226,357 cases hospitalized with primary HNC in Germany from 2005 to 2018 were included. Negative binomial regression was performed to study the development of the treatment rates over time. For all treatment options, i.e., biopsies, surgery, radiotherapy, and chemotherapy/biologicals, increases in the treatment rates were seen in patients >8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Men are about 3 times more likely than women to develop a head and neck cancer, mainly due to higher smoking and drinking rates.. The study also supported by (Kouka et al, 2023) who reported that Patients with head and neck cancer (HNC) are nearly 60% already over 60 years old and, approximately 70% are over 65 years and 50% over 70 years old.…”
Section: )supporting
confidence: 67%
“…Men are about 3 times more likely than women to develop a head and neck cancer, mainly due to higher smoking and drinking rates.. The study also supported by (Kouka et al, 2023) who reported that Patients with head and neck cancer (HNC) are nearly 60% already over 60 years old and, approximately 70% are over 65 years and 50% over 70 years old.…”
Section: )supporting
confidence: 67%